Human bcl-2 expression, cleaved caspase-3, and KSHV LANA-1 in Kaposi sarcoma lesions - da Silva, Suzane Ramos; Bacchi, Maura M.; Bacchi, Carlos E.; Oliveira, Deilson Elgui de [UNESP] (Amer Soc Clinical Pathology, 2007)
We aimed to evaluate the frequency of Kaposi sarcoma (KS)-associated herpesvirus (KSHV) infection in KS lesions in patients from Brazil. In addition, expression of human bcl-2, cleaved caspase-3, and KSHV latency-associated nuclear antigen (LANA)-1 in tumors was evaluated using inummohistochemical analysis. We studied 64 KS cases, classified as follows: classical, 20 (31 %); iatrogenic, 2 (3 %); AIDS-associated, 25 (39%); and not otherwise specified (lack of information about HIV status), 17 (27%). KSHV was detected by polymerase chain reaction (PCR) in 61 cases (95%); 40 cases (63%) were KSHV+ by PCR and immunohistochemical analysis for LANA-L Immunoexpression of bcl-2 was detected in 47 cases (73%). Only a few cells in 15 cases (23%) of KS had demonstrable immunostaining for cleaved caspase-3. These results further support the association of KSHV with all KS forms. Cleaved caspase-3 in KS tumors was infrequent, which may reflect the inhibition of apoptosis owing to bcl-2 overexpression observed in the majority of KS tumors.
Keywords: Kaposi sarcoma; Kaposi sarcoma-associated herpesvirus; KSHV; human herpesvirus 8; HHV-8; latency-associated nuclear antigen 1; cleaved caspase-3; human bcl-2